Model Predictive Sliding Surface Control of Voltage Source Inverter - Gulbudak, Ozan; Gökdağ, Mustafa; Komurcugil, Hasan (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper presents the model predictive sliding surface control strategy to control the voltage source inverter. The proposed control method benefits from the sliding mode control stability rule to shape the objective function of the optimization problem. The objective function is tailored such that the asymptotic stability criterion is used during the exploration of the optimum control input. The conventional model predictive control method is an effective control routine to handle multiple control goals. However, it can cause closed-loop instability in case of poor selection of the weighting factors or cost function. Due to this unfavorable characteristic of the conventional model predictive control method, the sliding mode control stability criterion is used as a control objective. The proposed objective function formulation guarantees the closed-loop stability regardless of the converter operation points such as power level. The proposed method does not require the weighting factors, which are usually necessary for the applications where the objective function is formed by two or more control goals, thus the system stability is improved. The proposed method is validated by the simulation works, and the results prove the effectiveness of the proposed control method. © 2022 IEEE
2022 IEEE International Conference on "Power Electronics, Smart Grid, and Renewable Energy", PESGRE 2022 -- 2022-01-02 through 2022-01-05 -- Virtual, Trivandrum -- 177643
Keywords: Model predictive control; Nine-Switch Converter; Optimal control; Sliding mode control